Refine design parameters for permanent magnet shape modification of the direct-drive generator - Noor Syazana Abd Ghani; Taib Ibrahim; Nursyarizal Mohd Nor (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The high cost associated with operation has promoted the progress of wave energy conversion and has higher power output and larger size. However, many countries are bordered by the sea, and the possible area for using wave energy is very small which can generate peak power generation systems with a power output of less than 100 W. The purpose of this article is to introduce the refined parameters of new design of the permanent magnet shape of with tubular longitudinal direct-drive generator. Three designs proposed, which different shapes of permanent magnets with same topology. The parameter optimization process was analysed using finite element analysis to determine the best main parameters of the design, namely the length of the stator length to translation ratio (????????/????????), pitch ratio (????????????/????????.), and split ratio (????????/????????). To evaluate design performance, electrical losses from the proposed design were also evaluated. The optimization results show these designs generator can produce 100 W of peak level output power with higher efficiency at rated current and optimal load.